Investigations of a Circularly Polarized Slotted Corner-Truncated Microstrip Patch Antenna with Split-Ring AMC Reflector - Chalanthon Ainthachot; Pisit Janpangngern; Sitthichai Dentri; Chuwong Phongcharoenpanich (My University, 2025)
This paper presents the design and development of a circularly polarized slotted corner-truncated microstrip patch antenna integrated with a split-ring artificial magnetic conductor (AMC) metasurface for WLAN applications at 2.45 GHz. The antenna design incorporates structural adaptations, such as slotted apertures and corner truncations, to enhance impedance matching and achieve circular polarization. To further improve performance, a split-ring AMC metasurface was employed, resulting in enhanced polarization purity and bandwidth. The proposed design achieves an impedance bandwidth (|S11| below −10 dB) from 2.33 GHz to 2.75 GHz and an axial ratio (AR) below 3 dB over the frequency range of 2.40 GHz to 2.55 GHz, and a peak gain of approximately 4.40 dBic at 2.45 GHz. Simulated results are validated by measured results of the fabricated prototype, demonstrating close agreement and confirming the robustness of the design methodology. This work highlights an innovative approach to compact and high-performance antenna design, ensuring its suitability for modern WLAN communication systems.
Keywords: Antenna Design and Analysis; Energy Harvesting in Wireless Networks; Advanced Antenna and Metasurface Technologies